School Branding Strategy in the Digital Era to Increase Engagement Through Digital Marketing - Muhammad Ridlo; Hadiah Fitriyah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The increasingly fierce competition among educational institutions requires schools to implement effective branding strategies to attract public interest. This study aims to analyze the digital branding strategy of SDI Tarbiyatul Ummah in increasing engagement through digital marketing, as well as to explore collaboration opportunities with its parent foundation, Yayasan Al-Manshur Tarbiyatul Ummah. This qualitative research collected data through in-depth interviews, observations, and documentation involving the principal, social media team, and parents. The researcher also served as participatory observer as the foundation's social media manager. The results indicate that the branding strategy relies on daily activity documentation distributed organically through an electronic word-of-mouth (eWOM) mechanism by parents. The QUALITAS tagline (Qur'ani, Peduli, Berprestasi) has successfully formed a positive impression among parents, and social media plays two simultaneous roles: as a discovery medium for prospective parents actively seeking information, and as a confirmation medium for those who learned about the school through other channels. However, the effectiveness of this strategy is hindered by reactive content planning due to limited human resources (single-handler) in both the school and the foundation. A content gap was also identified between what the school produces and the actual informational needs of parents. Furthermore, collaboration between the school and the foundation remains one-way due to the lack of a coordination system at the technical operational level. This study recommends the development of a collaborative content calendar, content diversification responsive to parents' needs, optimization of TikTok as a discovery platform, and formalization of the foundation's role as an active strategic partner within the private school digital branding ecosystem.